A rare complication of eculizumab treatment for atypical hemolytic uremic syndrome - Cyran, Agnieszka Maria; Ogarek, Iwona; Kwinta-Rybicka, Joanna; Drożdż, Dorota (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Atypical hemolytic uremic syndrome (aHUS) is a rare, life-threatening disease characterized by uncontrolled activation of the complement system. The introduction of eculizumab, a monoclonal antibody that blocks the complement protein C5, has significantly improved patient prognosis. However, eculizumab treatment is associated with a risk of adverse effects. We report a severe and complex case of aHUS in a 4-year-old boy, triggered by viral infections (influenza A and parvovirus B19) and influenced by genetic predisposition. An unexpected complication – a severe rash following eculizumab administration – necessitated discontinuation of the drug. Given the patient’s genetic risk factors, crovalimab was planned as an alternative treatment in case of recurrence. At the one-year follow-up, the patient’s kidney function remained stable, indicating a favorable outcome. This case underscores the complexity of aHUS management, the importance of genetic screening, and the need for vigilance in monitoring adverse drug reactions.